Word initial fricative production in children with cochlear implants and their normally hearing peers matched on lexicon size. (1st December 2016) - Faes, Jolien; Gillis, Steven
ABSTRACT: Fricative production is affected in children with cochlear implants (CI) as compared to age-matched normally hearing (NH) children. However, the phonological development of children with CI is rarely compared to that of NH peers matched on lexicon size. We compare the early word initial fricative development of 10 children with CI and 30 NH children matched on lexicon size and on chronological age. Children with CI are expected to differ from their NH peers when they are matched on chronological age. But, are lexical development and phonological development commensurate in children with CI as they have been shown to be in NH children? Results show that fricative production in children with CI deviates from that of age-matched NH peers. The differences between both groups disappear when they were matched on lexicon size. Thus, phonological development in children with CI is similar to that of their NH peers with comparable lexicon sizes.